IMPROVING EARLY CHILDHOOD LANGUAGE DEVELOPMENT THROUGH PLAYING SCRAMBLE - Meilani, Muna; Hibana, Hibana (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Children's low level of language development makes parents worried because with language children can interact with other people. Playing scramble is one of the efforts to improve language development by providing opportunities for children to be creative in composing sentences. This research is descriptive qualitative research that aims to build knowledge through understanding and discoveries based on the results of the study with children in kindergarten. Data were collected through observations and interviews with TK Dharma Wanita Bhakti Negara, TK Pertiwi Taman Asri, and TK Harapan Setia Negara. Based on the results of the study revealed that language development has increased. The implications of playing scramble provide fun learning so that children are very enthusiastic about participating in language learning. Children have an increase in vocabulary and children can arrange words into sentences.